2020
DOI: 10.5194/acp-2020-779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Photochemical degradation of iron(III)-citrate/citric acid aerosol quantified with the combination of three complementary experimental techniques and a kinetic process model

Abstract: Abstract. Iron(III) carboxylate photochemistry plays an important role in aerosol aging, especially in the lower troposphere. These complexes can absorb light over a broad wavelength range, inducing the reduction of iron(III) and the oxidation of carboxylate ligands. In the presence of O2, ensuing radical chemistry leads to further decarboxylation, and the production of ·OH, HO2·, peroxides, and oxygenated volatile organic compounds, contributing to particle mass loss. The ·OH, HO2·, and peroxides in turn re-o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 57 publications
(90 reference statements)
1
22
0
Order By: Relevance
“…We used a triad of photochemical experiments to observe photochemical reaction cycles on the nanoscale and microscale in single particles and films including scanning transmission X-ray microscopy coupled with near-edge X-ray absorption fine structure (STXM/NEXAFS) spectroscopy, a single particle electrodynamic balance (EDB), and a coated-wall flow tube (CWFT). Our multifarious observations were supported by a recent photochemical reaction and diffusion (PRAD) model 28 , 29 . We observed that photochemically produced CCRs induce anoxia in the interior of viscous particles, effectively preserving CCRs under dry conditions.…”
Section: Resultssupporting
confidence: 80%
See 4 more Smart Citations
“…We used a triad of photochemical experiments to observe photochemical reaction cycles on the nanoscale and microscale in single particles and films including scanning transmission X-ray microscopy coupled with near-edge X-ray absorption fine structure (STXM/NEXAFS) spectroscopy, a single particle electrodynamic balance (EDB), and a coated-wall flow tube (CWFT). Our multifarious observations were supported by a recent photochemical reaction and diffusion (PRAD) model 28 , 29 . We observed that photochemically produced CCRs induce anoxia in the interior of viscous particles, effectively preserving CCRs under dry conditions.…”
Section: Resultssupporting
confidence: 80%
“…These low β values are indicative of LMCT, i.e., charge transfer from the citrate ligand to Fe 3+ , forming Fe 2+ and a primary radical product, which immediately decays by decarboxylation (i.e., the removal of a carboxyl group via loss of CO 2 ). Then, an organic, carbon-centered radical, the primary CCR, is left behind 28 . Following the reaction steps in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations